1988
DOI: 10.2170/jjphysiol.38.19
|View full text |Cite
|
Sign up to set email alerts
|

Osmoreceptor mechanism for oxytocin release in the rat.

Abstract: In order to determine whether oxytocin release is controlled by an osmoreceptor mechanism identical with that for vasopressin release, the plasma oxytocin concentration and plasma osmolality were measured during intraatrial infusion and after intraventricular injection of various osmotic solutions in unanesthetized rats. Intraatrial infusion of 0.6 M NaCI Locke solution (LS.) or 1.2 M mannitol L.S. elevated plasma oxytocin significantly, while 1.2 M urea L.S. caused only a small increase and isotonic L.S. did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…Lesion studies have shown the participation of important brain nuclei in the oxytocin and vasopressin regulation. For example, the destruction of osmoreceptors in the OVLT and AP eliminates secretion of AVP and OT induced by the sodium loads administered (20,35). SON and PVN receive afferent fibers from the brain stem, such as NTS, LPBN, and raphĂ© nucleus (5-HT afferent), which carry visceral and cardiovascular information (1,18,41).…”
Section: Effect Of Induced Isotonic Vs Hypertonic Sodium Intake On Pmentioning
confidence: 99%
“…Lesion studies have shown the participation of important brain nuclei in the oxytocin and vasopressin regulation. For example, the destruction of osmoreceptors in the OVLT and AP eliminates secretion of AVP and OT induced by the sodium loads administered (20,35). SON and PVN receive afferent fibers from the brain stem, such as NTS, LPBN, and raphĂ© nucleus (5-HT afferent), which carry visceral and cardiovascular information (1,18,41).…”
Section: Effect Of Induced Isotonic Vs Hypertonic Sodium Intake On Pmentioning
confidence: 99%
“…56: [336][337][338][339][340] 2010) xytocin (OT) is synthesized in the cell body of the OT cell in the hypothalamic paraventricular (PVN) and supraoptic nuclei (SON) and released into blood circulation from axon terminals in the neurohypophysis. Various kinds of physiological stimuli such as parturition, lactation, osmotic stimulus and stress are known to stimulate OT secretion [1][2][3][4]. In lactating rats, OT is released intermittently as a result of periodic and synchronized activation of OT cells distributed in both sides of the hypothalamus, whereas pups suck nipples continuously [5].…”
mentioning
confidence: 99%
“…Recent studies have indicated that the anteroventral region of the third ventricle may represent an important source of afferents for the osmotic regulation of the hypothalamo-neurohypophysial system. In particular, lesions encompassing the organum vasculosum lamina terminalis (OVLT) have been found to attenuate the secretion of both oxytocin (Russell, Hatton & Robinson, 1984;Blackburn, Leng & Russell, 1986;Negoro, Higuchi, Tadokoro & Honda, 1988;Leng, Blackburn, Dyball & Russell, 1989) and vasopressin (Russell et al 1984;Leng et al 1989), and to attenuate the electrical response of MNCs following rises in systemic osmolality (Chaudhry, Dyball, Honda & Wright, 1989;Leng et al 1989). These findings have been supported by anatomical (e.g.…”
mentioning
confidence: 99%